2022
DOI: 10.56294/mr202219
|View full text |Cite
|
Sign up to set email alerts
|

The generation of transmedia content from the analysis of the image in tourism, an approach to the publication in social networks

Abstract: The aim of this article is to make the different components of the tourism product visible through a promotional strategy that reflects the different factors of the image and brings a possible consumer closer to a first impression of the destination. Therefore, by using the social network Instagram and generating transmedia content, the aim is not only to promote tourism but also to address elements that arise from tourism research, using social networks as a socializing mechanism for the activity. The publica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 17 publications
(13 reference statements)
1
1
0
Order By: Relevance
“…22,45 Furthermore, professionals use it worldwide. 23,46,47 Based on the results of the present study, a positive and significant association is demonstrated between the four main areas of entrepreneurs' businesses proposed by Keane et al (2018) 33 and the nine modules of the Business Model Canvas. Additionally, the chi-square test showed dependent relationships between the four business areas and the BMC.…”
Section: Discussionsupporting
confidence: 65%
“…22,45 Furthermore, professionals use it worldwide. 23,46,47 Based on the results of the present study, a positive and significant association is demonstrated between the four main areas of entrepreneurs' businesses proposed by Keane et al (2018) 33 and the nine modules of the Business Model Canvas. Additionally, the chi-square test showed dependent relationships between the four business areas and the BMC.…”
Section: Discussionsupporting
confidence: 65%
“…The oil spill in Ancón occurred on January 15, 2022, when the tanker Mare Doricum was unloading at the facilities of dock 2 Multiboyas of La Pampilla SAA refinery, in charge of Repsol Petróleos. This spill has been catalogued as the worst recent ecological disaster in Lima, affecting 48 beaches in the regions of Ventanilla, Santa Rosa, Ancon, Aucallama, Chancay and Huacho [4][5][6] . The consequences of this spill have been devastating for the marine environment.…”
Section: Introductionmentioning
confidence: 99%